Situational Analysis of the Rights of Persons with Disabilities in the Republic of North Macedonia – 2021 - Kochoska, Elena; Jovanovska, Bojana; Ortakovski, Tomislav; Stanojkovska Trajkovska, Natasha; Georgievska, Sofija (United Nations, 2022)
The Republic of North Macedonia ratified the United Nations Convention on the Rights of Persons with Disabilities (CRPD) in 2011. In the following period, the rights of persons with disabilities were advanced because of the ongoing reforms in social protection and education, and developments in the areas of non-discrimination, inclusive employment services, deinstitutionalization, access to sexual and reproductive health services, prevention of genderbased violence and promotion of gender equality. A political will to ensure active participation of persons with disabilities is evident and reflected in the legislative framework. The 2019 Social Protection Law promotes the principle of equal treatment and non-discrimination in the realization of social protection rights, which are based on equal and just treatment, recognizing disability as a basis for discrimination. The new Social Protection Law and a major revision of the Child Protection Law overhauled and consolidated the cash benefit system to, among other things, ensure increased coverage and adequacy. The reform also introduced new social support and care services for persons with disabilities and their caregivers. With the undertaken reforms in education, the state strives for all children with disabilities to be included in regular primary education. The state has also provided financial resources and hired 500 education assistants for children and youth with disabilities through primary schools with a resource centre. The system of assessment according to the International Classification of Functioning (ICF) for children and youth up to 26 years of age has recently started to be successfully implemented, in four of the eight planning regions. However, the transition to ICFbased assessment as the single-entry point into the system of cash benefits and support services cannot be completed until assessment bodies are established in all regions. The process of deinstitutionalization is ongoing, albeit not in line with article 19 of the CRPD. The process has been completed for children, with no children left in large-scale institutions in the country. Children without parental care are eighter in foster care, or small group homes. However, there are still persons with disabilities over 18 years of age in institutions. Generally, the process of deinstitutionalization should depart from the goal of closing large institutions and move towards provision of accessible and affordable housing, modern technical aids, personal assistance, and peer support, which will improve self-confidence of the persons with disabilities and their capacity to become fully included in society. Considering the previous developments and achievements, this situational analysis uses the CRPD lens to identify seven main bottlenecks and challenges in the realization of fundamental human rights of the persons with disabilities, and the basic preconditions for the inclusion of disability in the society.
Keywords: Persons with disabilities, United Nations Convention on the Rights of Persons with Disabilities (CRPD), Situational analysis